IMPLEMENTATION OF THE GUIDEBOOK IN MUARA KONOCO LESTARI TOURISM AWARENESS GROUP ACTIVITIES - Ilhami, M. Ridha; Ayurizky, Nona; Arisanty, Deasy; Angriani, Parida; Abbas, Ersis Warmansyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
The Muara Konoco Lestari Tourism Awareness Group (Pokdarwis) as a formal institution must of course carry out activities in accordance with the guidelines of the tourism awareness group. The research aims to describe the activities carried out by the Muara Konoco Lestari Tourism Awareness Group per the guidelines of the tourism awareness group book. This research uses a qualitative approach. Data collection techniques include observing Pokdarwis activities, interviewing informants, and documentation. Data analysis starts from reduction, presentation and verification. Based on the guidebook for tourism awareness groups, there are six areas of activity that tourism awareness groups can implement. The results of the research show that Pokdarwis activities related to the guidelines implemented by Muara Konoco Lestari Pokdarwis still take the form of: 1. increasing the knowledge and insight of Pokdarwis members in the field of tourism; 2. Increasing the abilities and skills of members in managing the tourism business sector and other related businesses. Meanwhile, activities that have yet to be carried out are related to the Pokdarwis guidelines: 1. Encouraging and motivating the community to become good hosts in supporting tourism activities in their area; 2. Encourage and motivate the community to improve the quality of the environment and local tourism attractions through efforts to activate Sapta Pesona; 3. Collect, process and provide tourism information services to tourists and local communities; and 4. Providing input to government officials in developing tourism in the local area. The conclusion of the research is that several Pokdarwis function activities still need to be implemented optimally, so further action is needed so that the Muara Konoco Lestari tourism awareness group can implement activities based on the Pokdarwis guidebook.